Perceptions and attitudes among interns of dental colleges in Pune district toward community outreach program: A qualitative study - Pranav Pramod Shinde; Sahana Hegde Shetiya; Deepti Agarwal; Anmol Mathur (Wolters Kluwer Medknow Publications, 2018)
Background: Dental Council of India in its 3rd amendment regulations-2011 had incorporated 3 months of compulsory rural posting for the dental interns to sensitize them toward social responsibility through community outreach program. Objective: The objective of the present qualitative study was to understand in-depth the perceptions and attitudes of the interns of dental colleges in Pune district, India, toward community outreach programs. Materials and Methods: Focused group discussions were conducted for each group of ten interns separately in one college for about 1 hour, based on a well-designed but flexible topic guide through a moderator and a note-taker. Results: Most of the interns were aware of need for outreach programs in the community. It helps the interns in sharpening their clinical as well as communication skills outside the traditional dental school settings. Since most of the dentists prefer to practice in urban or financially stable areas, such programs can increase the exposure of dental students to underserved population and sensitize them toward their oral health needs. Conclusion: Thus, dental profession must develop strategies to provide new graduates with professional and personal support to retain the rural dental workforce.